Trends in Soil Carbon Stockpile of Three Major Forests Along an Altitudinal Gradient in Indian Central Himalaya - Bohra, CS; Tewari, SK; Bhatt, MD (Ecoprint: An International Journal of Ecology, 2015)
Current investigation reveals the stock of soil organic carbon (SOC) along with altitudinal gradients in Oak (Quercus leuchotrichophora), Pine (Pinus roxburghii) and Sal (Shorea robusta) dominant forests in Shiwalik region of Kumaun Himalayas in India. The estimated soil organic carbon was found 16.0 ± 4.3 to 19.4 ± 6.4 g kg-1 for Oak, 17.8 ± 2.0 to 25.6 ± 1.6 g kg-1 for Pine and 15.8 ± 2.2 to 21.4 ± 1.9 g kg-1 for Sal forests, respectively in 0-10, 10-20 and 20-30 cm soil depths. SOC stock was found to be in decreasing pattern with increasing altitude from 193.6 to 166.4, 146.4 to 137.6 and 159.2 to 141.6 t C ha-1 in Oak, Pine and Sal forests, respectively. It is an indicator of higher biological activity or anthropogenic disturbance associated with top layers of these forest areas. Higher SOC was recorded in Sal forest compared to Oak. In Sal forest, high tree density leads to higher accumulation of SOC compared to conifers while it was low in wide spread Pine forest, resulting in less storage of carbon stock in turn. ECOPRINT 21: 7-13, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11898